Influence of the substrate of green roofs in the reduction of surface runoff when subjected to the climatic conditions of the Metropolitan Region of Recife (Research, Society and Development, 2021)
The urbanization process results in a reduction of permeable areas, generating a reduction in the infiltration rate and consequent increase in flow rainwater, intensifying the frequency and magnitude of flooding. However, the use of green roofs has been proving to be an efficient practice in reducing and delayed this flow. In this sense, we sought to identify the optimal textural class for the substrate of a green roof submitted to the climatic conditions of the Metropolitan Region of Recife (RMR). Then, the Hydrus-1D model was calibrated and validated using the volume drained by a green roof prototype. Then simulations of the soil water flow with different textural classes were made. After validation, a good efficiency of the model was verified in the representation of the observed values. Finally, the textural classes that presented the highest average retention capacities were sandy loam, loam, silt loam and silt. Therefore, for the studied region, the green roof substrate should be composed of one of these soil categories. In the absence of them, sand, loamy sand, silty clay loam or clay loam should be employed.